Effect of Preoperative Steroid Injection on Wound Drainage after Modified Radical Mastectomy - Muhammad Nasir Iqbal, Amir Usman, Sommayya Aftab, Mansab Ali, Syed Muhammad Mohsin Azeem, Wafa Najeeb, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: After surgery for breast cancer, there is a risk of increased wound drainage and seroma formation. Various treatments are utilized to overcome this issue with variable effectiveness. Objective: To compare the outcome of a single preoperative dose of intravenous steroid injection versus control group on wound drainage in patients undergoing modified radical mastectomy (MRM) for stage I and II breast cancer. Methodology: It is a randomized control trial conducted over a period of 6 months. Total 60 patients who underwent MRM for carcinoma of breast were included. They were divided into 2 groups with each group having 30 cases. In group-A 120 mg (3 ml) of injection depomedrol was given one hour before surgery while in group B, 3 ml of normal saline was used, and MRM was performed and two drains were placed. At the time of drain removal, drainage volume was assessed in both groups. Results: Mean age of the patients was 47.37.89 and the mean drainage volume in group A versus B was 672117.63 and 1020159.9 respectively. Among the patients, 51.7% had stage I and 48.3% had stage II breast cancer. The two groups had statistically significant difference in terms of mean drainage volume (p value =0.048). Conclusion: In patients who underwent MRM, prophylactic steroid injection was associated with significant reduction in mean drainage volume compared to normal saline. Keywords: Modified Radical Mastectomy, Steroid, Seroma Formation